Hilangnya Objek Jaminan Fidusia yang Tidak Didaftarkan - Kadek Cinthya Dwi Lestari; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2020)
Abstractâ€”In accordance with the provisions in the Fiduciary Guarantee Law, the object of fiduciary guarantee must be registered at the fiduciary registration office, but in practice there are still many who do not register it. â€œThe Loss of the Unregistered Fiduciary Objectâ€ has the formulation of the problem as a result of the legal guarantee dispute resolution effort the loss of unregistered fiduciary collateral objects. This research method uses mixed legal research method. In this type of legal research, combining between norm-based events and actual occurrences can be conclude that no fiduciary collateral results in the creditor not having preferential rights and executorial title rights in the case of destruction, the object of human guarantee can be resolve by litigation and non-litigation. This method combines the implementation of normative legal provisions (laws) in its action on certain legal events that occur in a society. After conducting this analysis, it can be concluded that the failure to register a fiduciary guarantee causes the creditor not to have preferential rights and executorial title rights. In the event that the destruction of the object of fiduciary guarantee can be resolve by means of litigation and non-litigation. At BPR Artha Bali Jaya, the settlement is carried out by non-litigation, namely by means of family or mediation, where if the debtor continues to pay the remaining credit, the lost object is not dispute. And to further reduce risk BPR Artha Bali Jaya asks debtors to replace lost collateral objects by pledging other objects of the same value.